MENUMBUHKAN RASA SENANG BERHITUNG DENGAN METODE JARIMATIKA PADA PESERTA DIDIK TK - Kurniawan, Choirul (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2020)
This study aims to measure and foster a sense of pleasure in counting with the jarimatika method. This research is a classroom action research. Techniques for data collection consist of observation sheets, interviews and documentation. Analysis techniques using variables that have been made include aspects of activeness in the classroom and how students use their fingers when learning takes place. Based on research that has been done, it is known that jarimatika learning can help students foster a sense of pleasure in learning mathematics and as a result students are able to use their fingers to count. The method of using fingers is very easy for students to do especially in kindergarten age, moreover it is supported by counting tricks by using fingers which are very preferred by children.